The democracy index : why our election system is failing and how to fix it - Gerken, Heather K., 1969- (Princeton University Press, 2009)
Despite howls for reform, the only thing separating us from another election disaster of the kind that hit Florida in 2000, and that almost struck again in Ohio in 2004, may simply be another close vote. In this lucid and lively book, Heather Gerken diagnoses what is wrong with our elections and proposes a radically new and simple solution: a Democracy Index that would rate the performance of state and local election systems. A rough equivalent to the U.S. News and World Report ranking of colleges and universities, the Index would focus on problems that matter to all voters: How long does it t.